(untitled) (Research, Society and Development, 2020)
Social skills are often correlated with mental health índex. The present study aimed to verify correlations between stress, depression and social skills of military police officers. The study was conducted by 129 police officers (93% men), with a mean age of 29.71 years (Standard Deviation=4.88) who answered a sociodemographic form, Perceived Stress Scale – PSS-14, Patient Health Questionnaire-9 – PHQ-9 and Social Skills Inventory – IHS-Del-Prette. The results showed that the most frequent situations of greater stress in military police work were lack of professional recognition and interpersonal relationships, which represented almost half (45.8%) of the answers, leaving in second place the discomforts with the main activities. The comparison between the means of psychological stress and depression by sex revealed statistically significant differences (p<0.05), with women reporting higher levels of psychological stress and depression than men, although they did not differ in social skills (p=0.486), reaching on average good repertoire for both. The prevalence of social skills deficit was 27.1% and 10.9% for depression, with psychological stress level (Mean=22.67; Standard Deviation=7.76) below the reference mean point. There was a significant and negative correlation between the total score of social skills with stress (p<0.001) and with depression (p<0.01), as well as a significant and positive correlation between stress and depression (p<0.001). It was discussed the need of monitoring psychological stress and depression in the exercise of military activity, in addition to training social skills aimed at protecting and promoting the military police officers’ mental health.